2006
DOI: 10.2337/diabetes.55.04.06.db05-1286
|View full text |Cite
|
Sign up to set email alerts
|

Group 1B Phospholipase A2–Mediated Lysophospholipid Absorption Directly Contributes to Postprandial Hyperglycemia

Abstract: Postprandial hyperglycemia is an early indicator of abnormality in glucose metabolism leading to type 2 diabetes. However, mechanisms that contribute to postprandial hyperglycemia have not been identified. This study showed that mice with targeted inactivation of the group 1B phospholipase A 2 (Pla2g1b) gene displayed lower postprandial glycemia than that observed in wild-type mice after being fed a glucose-rich meal. The difference was caused by enhanced postprandial glucose uptake by the liver, heart, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 32 publications
5
113
0
Order By: Relevance
“…However, group IB sPLA 2 deficiency does not lead to alterations in basal or glucose-stimulated insulin secretion in mice (38) and group IIA sPLA 2 is naturally deficient in the inbred C57BL/6 mouse strain (39), ruling out a role for these two isozymes in the current study. We determined by real time RT-PCR that GV and GIID sPLA 2 mRNAs are expressed by MIN6 cells, whereas group III, group XIIA, and group XIIB mRNAs were not detected (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…However, group IB sPLA 2 deficiency does not lead to alterations in basal or glucose-stimulated insulin secretion in mice (38) and group IIA sPLA 2 is naturally deficient in the inbred C57BL/6 mouse strain (39), ruling out a role for these two isozymes in the current study. We determined by real time RT-PCR that GV and GIID sPLA 2 mRNAs are expressed by MIN6 cells, whereas group III, group XIIA, and group XIIB mRNAs were not detected (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…One of the major pathways for the formation of LPA is through the action of autotaxin on LysoPC ( 23 ). A major source of intestinal LysoPC is through the action of PLA2G1B (45)(46)(47)(48)(49)(50). PLA2G1B is a pancreatic PLA 2 that hydrolyzes fatty acids at the sn -2 position of phospholipids in the lumen of the small intestine.…”
Section: Searching For Natural Sources Of Intestinally Derived Lpamentioning
confidence: 99%
“…Recent studies employing transgenic (Tg) (gain-of-function) and knock-out (loss-offunction) mice for several sPLA 2 s have revealed that individual enzymes exert distinct functions in vivo. Thus, PLA2G1B (group IB sPLA 2 ) plays a role in digestion of dietary phospholipids (3,4), PLA2G2A (group IIA sPLA 2 ) plays a role in antibacterial defense and possibly tumorigenesis (5)(6)(7)(8), PLA2G5 (group V sPLA 2 ) plays a role in zymosan-induced eicosanoid synthesis and phagocytosis by macrophages (9,10) and airway hypersensitivity (11), and PLA2G10 (group X sPLA 2 ) plays a role in allergen-induced asthma (12) and myocardial ischemia/ reperfusion injury (13). Thus far, beyond the well accepted regulatory role of group IVA cytosolic PLA 2 in arachidonate metabolism (14), PLA2G5 and PLA2G10 are the only two sPLA 2 s that have been proven to have the capacity to modulate arachidonic acid metabolism in vivo (15,16).…”
mentioning
confidence: 99%